SpoVID Guides SafA to the Spore Coat in Bacillus subtilis - Ozin, Amanda J. (American Society for Microbiology, 2001)
Bacteria assemble complex structures by targeting proteins to specific subcellular locations. The protein coat that encases Bacillus subtilis spores is an example of a structure that requires coordinated targeting and assembly of more than 24 polypeptides. The earliest stages of coat assembly require the action of three morphogenetic proteins: SpoIVA, CotE, and SpoVID. In the first steps, a basement layer of SpoIVA forms around the surface of the forespore, guiding the subsequent positioning of a ring of CotE protein about 75 nm from the forespore surface. SpoVID localizes near the forespore membrane where it functions to maintain the integrity of the CotE ring and to anchor the nascent coat to the underlying spore structures. However, it is not known which spore coat proteins interact directly with SpoVID. In this study we examined the interaction between SpoVID and another spore coat protein, SafA, in vivo using the yeast two-hybrid system and in vitro. We found evidence that SpoVID and SafA directly interact and that SafA interacts with itself. Immunofluorescence microscopy showed that SafA localized around the forespore early during coat assembly and that this localization of SafA was dependent on SpoVID. Moreover, targeting of SafA to the forespore was also dependent on SpoIVA, as was targeting of SpoVID to the forespore. We suggest that the localization of SafA to the spore coat requires direct interaction with SpoVID.